Transient and long-term antioxidant gene responses in Medicago truncatula following application of exogenous nitric oxide - Fotopoulos, Vasileios; Mylona, Photini V.; Polidoros, Alexios N. (My University, 2009)
Nitric oxide (NO) is a bioactive molecule involved in many biological events that has been reported to act as both a prooxidant and an antioxidant in plants. Several reports exist which investigate the protective action of low (f.lM) concentrations of sodium nitroprusside (SNP), a NO donor. It is now commonly accepted that NO acts as a signal molecule in plants possibly playing a role to induce/stabilize the expression of many antioxidant enzymes. This study attempts to provide novel insight into the effect of application of exogenous NO on transient and long-term antioxidant gene expression levels in the model plant Medicago truncatula following inhibition studies and a quantitative real-time peR approach. Our data suggest that exogenous NO leads to a transient (3hour) induction of several antioxidant genes examined including A ox, Apx and Cat, while expression levels appear to decline after 24 hours. NO- and ROS-dependent signalling pathways were detected to operate and differentially affect induction of the different antioxidant genes. Our data suggest that Cat expression is not affected directly by NO or ROS-signalling cascades. Aox induction by NO is affected by NO- and ROS-dependent signalling pathways while Apx induction by NO has NO-dependent but not ROS-dependent signalling components.
Keywords: Oxidative stress; Nitric oxide; Sodium nitroprusside